Class II malocclusion nonextraction treatment with growth control - Assunção,Zilda Lúcia Valentim (2014)
The present study reports a case of Angle Class II malocclusion treatment of a male growing patient with 10-mm overjet, excessive overbite and transverse maxillary deficiency. The case was presented to the Brazilian Board of Orthodontics and Dentofacial Orthopedics (BBO), with DI equal to or greater than 10, as a requirement for the title of certified by the BBO.